Dosimetric implications associated to heterogeneity dose correction in stereotactic body radiation therapy (SBRT) of lung cancer (Revista de Física Médica, 2016)
Treatment of lung lesions using stereotactic body radiation therapy (SBRT) requires algorithms with corrections that adequately model the behavior of narrow beams in the presence of tissue heterogeneities, although protocols such as RTOG 0236 excluded these kind of corrections.100 cases were evaluated retrospectively following the RTOG 0813 and RTOG 0915 guidelines, by obtaining the deviations of the relevant dosimetric indicators from Monte Carlo (MC) and Pencil Beam (PB), maintaining the same configuration and monitor units (MU).Deviations between MC and PB have been classified according to the volume and density of the lesion. The greatest variations (up to 45% difference in D50%) are found for cases with lower volume and density, where the lesion is almost equivalent to lung tissue, given the higher proportion of air surrounding the periphery of the tumor, and the reduction of the radiation fields, resulting in a lack of electronic equilibrium that must be properly considered in the treatment planning system.These deviations involve dosimetric implications which are observable in clinical outcomes, determining how to proceed in treatment planning, to ensure that the actual dose delivered is performed accordingly to the prescription dose, while requiring the use of algorithms with a proper heterogeneity correction.